Debbie Shore's SEWING ROOM SECRETS : Machine Sewing - Shore, Debbie (Tumbridge Wells, Kent : Search Press Limited, 2019)
"Whether you are just starting out or are an enthusiastic sewer looking to perfect your skills, step into Debbie Shore's sewing room and learn all the techniques you need for successful machine sewing. Jam-packed with friendly advice and helpful tips, Debbie walks you through every aspect of machine sewing, including deciding which machine to buy, inserting a zip, making bias binding and free-motion embroidery. She guides you through the wonderful array of fabrics, threads, wadding and interfacing available and builds your confidence and skills as you progress through the book with ten gorgeous step-by-step projects. You will turn to this book again and again!"--Page 4 of cover.
Includes index
Keywords: Machine sewing; Machine sewing -- Technique